Redesain User Interface Aplikasi BCA Mobile Banking Menggunakan Metode Design Thinking - Abimanyu, Silvan; Sutopo, Joko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Bank Central Asia (BCA) is a leading conventional private financial institution in Indonesia, with the number of customer accounts reaching 34.68 million individuals in 2022. This number has increased by 21.68% compared to the previous year when there were 28.5 million customers. In managing its business operations, BCA responds to technological developments by presenting the BCA Mobile Banking application. Even though this application aims to simplify the transaction process and meet customer needs, several shortcomings affect the level of user satisfaction, especially related to the appearance of the User Interface (UI) and User Experience (UX), which are considered less dynamic and modern. This research aims to redesign the appearance of the BCA Mobile Banking application, with a focus on improving aspects of modernity and user comfort, especially for customers from Generation Z. To achieve this goal, this research applies Design Thinking and Lean UX methods, with an audience orientation. The main one is Generation Z who tends to appreciate simple and minimalist designs.